Vägen mot demokrati: Polen och Belarus efter Kommunismens fall - Adébo,Adam; Ohlsson,Elias (2025)
The collapse of the Soviet Union and the Warsaw Pact suddenly made it possible for the former communist states of eastern Europe to become democratic free states. However, the process of democratisation has been varied across different countries despite similarities. This essay aims to contribute to the research of democratisation processes in neighbouring countries by studying the cases of Poland and Belarus, and examining how one could develop a working democracy while the other has stuck with authoritarian rule. The research is done through process tracing where key events are studied and then analysed with theories of democratisation and the effects of external actors. The main factors for the different outcomes comes from a difference in societal pressure, as well as external pressure being a factor in sustaining authoritarian rule in Belarus and in consolidating Poland’s democracy.
Keywords: Demokratisering; auktoritarism; mobilisering; civilsamhälle; postkommunism